Konsistensi Rencana Tata Ruang Permukiman Dan Arahan Kebijakan Pembangunan di Kabupaten Tanah Datar, Provinsi Sumatera Barat - Iswandi - Umar; Indang Dewata; Eri Barlian (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
In Indonesia the implementation of the spatial plan is only a small part of the plan. The impact of incompatibility with spatial planning is the deterioration of environmental quality. Tanah Datar District has a growth rate of settlements of 1.3 percent/year period 2000-2017. The purpose of this research is to determine index consistency of spatial plan and determination of policy direction of development of settlement area. To determine the consistency index of spatial planning to do a comparison between land use with the spatial plan. Land use map produced from Landsat ETM + 8, and map spatial plans resulting from the RTRW period 2008-2028 In Tanah Datar District. In addition, to determine the direction of the policy of settlement development using the ISM method. The number of elements analyzed by 10 elements, with 24 experts. The results show that around 43.7 percent ofsettlement development is incompatible with the spatial plan. Therefore, it is necessary for government policy to be consistent with spatial planning and law enforcement on spatial violations.